Binary Encounter Electrons in Fast Dressed-Ion–H2 Collisions: Distorted Wave Theories and Experiment - Nicolás J. Esponda; Stefanos Nanos; Michele A. Quinto; Theo J. M. Zouros; Roberto D. Rivarola; Emmanouil P. Benis; Juan M. Monti (Atoms, 2023)
We report measurements of double differential cross section for zero-degree binary encounter electrons emitted in collisions of 4.9 MeV and 13 MeV B<semantics>(2−5)+</semantics> ions with H2 targets. The corresponding calculations based on continuum distorted-wave (CDW) theories are critically compared to the measurements. CDW in its post form exhibits a very good agreement with the measurements in all cases. The CDW theories utilized along with the well-known eikonal-initial-state (CDW-EIS) approximation are also examined and their results are compared to both the measurements and the CDW calculations. In particular, CDW-EIS using a recently proposed dynamic effective charge for the final channel projectile distortion exhibits a substantial improvement in comparison with an effective net-charge approximation.